Depression, Alcoholism, and Genetic Alcohol Sensitivity Regulated by ALDH2 and ADH1B Polymorphisms among Japanese Community-Dwelling Adults - Kouichi Yoshimasu; Shigeki Takemura; Kanami Tsuno; Mariko Hayashida; Kenji Kinoshita; Kanae Mure; Tatsuya Takeshita; Kazuhisa Miyashita (Archives of Depression and Anxiety - Peertechz Publications, 2016)
Background: Although strong association between drinking and depression as well as alcohol- related disorders (ARD) has been reported, the relationship between potential ability to drink (genetic alcohol sensitivity) and depression or ARD is unclear. Genetic alcohol sensitivity is regulated by two alcohol metabolic enzyme genes, ADH1B and ALDH2 polymorphisms. We have already evaluated the  association  between  depression  and  these  polymorphisms  in Japanese white-collar  workers.Current study expanded this issue on community-dwelling relatively older adults. Methods: A total of 654 community-dwelling people were interviewed regarding their ARD by a brief psychiatric structured interview (MINI). Severity of depression was evaluated by the Center for  Epidemiologic  Studies  Depression  Scale  (CES-D). We investigated  the  relationship  of ADH1B rs1229984 and ALDH2 rs671 polymorphism combinations with depression and ARD risks. Logistic regression analysis was used to evaluate the associations between those polymorphisms and mental disorders, adjusting for sex, age, number of family members, physical exercise, job status, and serum lipid  abnormality. The degree of alcohol sensitivity  was  classified  into  five  groups  according  to  the combination of two enzyme genotypes (Group I-V, in order from the lowest alcohol sensitivity). Results: Those  with ALDH2 1 / * 2 and   ADH1B * 1 / * 1  were  likely  to  be  at  an  increased  risk  of depression  (OR  6.63,  95%  CI  1.12-39.21).  On  the  other  hand,  a  genotype  combination  of ALDH2 * 1 / * 1 and  ADH1B * 1 / * 2 or * 2 / * 2 was significantly associated with an increased risk of ARD (OR 3.93, 95% CI 1.86-8.31). Similar findings were observed when depression and ARD were combined as an  outcome variable. Conclusions: Genetic alcohol sensitivity  with  the genotype  combination  of ALDH2 * 1 / * 2 and ADH1B * 1 / * 1  was significantly  associated  with an  increased  risk  of  depression,  while  Japanese community-dwellers in rural areas with ALDH2 * 1 / * 1 and  ADH1B  * 1 / * 2 or * 2 / * 2 were at a  significantly elevated risk of ARD.